Environment-friendly snow-melting agent based on agricultural and forestry wastes
By preparing an environmentally friendly snow-melting agent based on agricultural and forestry waste, the problems of high cost, short duration, poor adhesion and strong corrosiveness of existing snow-melting agents have been solved. This has achieved a low-cost, long-lasting and environmentally friendly snow-melting effect, and improved the adhesion of the snow-melting agent and the safety of the road surface after snow melting.
Patent Information
- Application Number
- CN202610035423.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-12
- Publication Date
- 2026-05-15
AI Technical Summary
Existing de-icing agents suffer from problems such as high cost, short duration of action, poor adhesion, limited functionality, poor stability, and easy re-icing of roads after snow melting. Furthermore, traditional chloride-based de-icing agents are polluting and corrosive to the environment.
An environmentally friendly de-icing agent based on agricultural and forestry waste is used, which includes components such as agricultural and forestry waste combustion ash, food processing organic waste liquid, polyol, filler, agricultural waste fiber, synthetic pulp, polyacrylate water absorbent and binder. It is prepared through a specific process to form a de-icing agent with high adhesion, long duration and environmental protection.
It reduces production costs by 25-30%, extends snow melting time by more than 50%, improves adhesion and snow melting efficiency, reduces the probability of secondary icing, reduces corrosion to roads and metals, and meets environmental protection requirements.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention relates to the field of snow-melting agent preparation technology, specifically to an environmentally friendly snow-melting agent based on agricultural and forestry waste. Background Technology
[0002] Winter snow and ice weather easily leads to snow accumulation and icing on roads, seriously threatening traffic safety. Snow-melting agents, as the core material for snow and ice removal, are widely used in highways, airports, and municipal roads. While traditional chloride-based snow-melting agents have high snow-melting efficiency, they have significant drawbacks: they easily cause soil salinization, corrode road infrastructure and vehicle metal parts, and pollute groundwater. Meanwhile, some environmentally friendly snow-melting agents face problems such as short melting time, easy splashing and runoff, easy re-icing of roads after snow melting, and high costs.
[0003] In the existing technological system, some research teams have prepared snow-melting agents using methyl glycosides, alcohol residues, and calcium carbonate powder as raw materials. However, natural calcium carbonate requires multiple pretreatment processes such as crushing and grinding, making the process cumbersome and the production cost high. Furthermore, the snow-melting efficiency of calcium carbonate is significantly limited. Another technical route uses a mixture of concentrated acetic acid solution and wood ash as the core snow-melting component. However, acetic acid is expensive, and unreacted free acetic acid can seep into the soil environment with the snowmelt runoff, causing soil acidification and adversely affecting the normal growth and development of surrounding vegetation. In addition, the weakly acidic nature of acetic acid can accelerate the electrochemical corrosion process of metal components such as road guardrails and vehicle chassis.
[0004] With tightening environmental policies and increasing demands for sustainable development, developing environmentally friendly snow-melting agents that combine low toxicity, no pollution, stable snow melting, controllable cost, and infrastructure friendliness has become a pressing technical challenge for the industry. Summary of the Invention
[0005] To address the aforementioned shortcomings of existing technologies, this invention provides an environmentally friendly snow-melting agent based on agricultural and forestry waste, which effectively solves the problems of high cost, short duration, poor adhesion, limited functionality, poor stability, and easy re-icing of roads after snow melting.
[0006] To achieve the above objectives, the technical solution adopted by the present invention to solve its technical problem is: to provide an environmentally friendly snow melting agent based on agricultural and forestry waste, comprising the following components by weight: 150-250 parts of agricultural and forestry waste combustion ash, 750-850 parts of food processing organic waste liquid, 180-220 parts of polyol, 100-200 parts of filler, 60-65 parts of agricultural waste fiber, 7-8 parts of synthetic pulp, 7-8 parts of polyacrylate water absorbent, 90-110 parts of binder, and 4-6 parts of activated clay.
[0007] Furthermore, the aforementioned environmentally friendly snow-melting agent based on agricultural and forestry waste includes the following components by weight: 200 parts of agricultural and forestry waste combustion ash, 800 parts of food processing organic waste liquid, 180 parts of polyol, 150 parts of filler, 60 parts of agricultural waste fiber, 7.5 parts of synthetic pulp, 7.5 parts of polyacrylate water absorbent, 100 parts of binder, and 5 parts of activated clay.
[0008] Furthermore, the ash from the combustion of agricultural and forestry waste is one of the following: wood ash, straw ash, and dead branch ash.
[0009] Furthermore, the organic waste liquid from food processing is either alcohol residue or vinegar residue.
[0010] Furthermore, the polyol is a liquid methyl glucoside or crude glycerol.
[0011] Furthermore, when the polyol is a liquid methyl glucoside, the environmentally friendly snow-melting agent based on agricultural and forestry waste does not contain activated clay.
[0012] Furthermore, when the polyol is crude glycerol, the environmentally friendly de-icing agent based on agricultural and forestry waste contains activated clay.
[0013] Furthermore, the filler is one of diatomaceous earth, bentonite, and zeolite powder.
[0014] The beneficial effects of taking the above-mentioned further steps are that diatomaceous earth, bentonite, and zeolite powder can prevent caking and enhance adhesion and adsorption.
[0015] Furthermore, agricultural waste fiber is one of corn stalk fiber, wheat stalk fiber, and rice husk fiber.
[0016] Furthermore, the ash from the combustion of agricultural and forestry waste passes through an 80-mesh sieve, with a potassium content ≥10 wt% and a moisture content ≤5 wt%.
[0017] Furthermore, the organic waste liquid from food processing contains 20-50 vt% ethanol, ≥20000 mg / L acetic acid, and a pH value of 3-5.
[0018] Furthermore, the liquid methyl glucoside is industrial grade, with a purity ≥98 wt% and a density of 1.18-1.22 g / cm³. 3 Viscosity (25 ℃) 50-80 mPa s.
[0019] Furthermore, the crude glycerol is industrial grade, with a purity ≥80 wt% (biodiesel byproduct), methanol content ≤0.5 wt%, and fatty acid content ≤5 wt%.
[0020] Furthermore, the diatomaceous earth is industrial grade, passes through an 80-mesh sieve, has a particle size of 5-20 μm, and a specific surface area ≥20 m². 2 / g, moisture content ≤8 wt%.
[0021] Furthermore, the bentonite is of industrial grade, with a particle size of 10-30 μm and a specific surface area ≥15 m². 2 / g, moisture content ≤8 wt%.
[0022] Furthermore, the corn stalk fiber passes through an 80-mesh sieve, has a cellulose content of ≥70 wt%, and is free from mold growth after drying.
[0023] Furthermore, the wheat straw fiber passes through an 80-mesh sieve, has a cellulose content of ≥65 wt%, and is free from mold growth after drying.
[0024] Furthermore, the synthetic pulp is industrial grade, with a polyester fiber content of ≥95 wt% and a length of 1-3 mm.
[0025] Furthermore, the polyacrylate superabsorbent is of industrial grade, with a water absorption ratio of ≥300 times and a particle size of 100-200 mesh.
[0026] Furthermore, the adhesive is an alcohol solution or an ethylene glycol solution.
[0027] Furthermore, the concentration of the alcohol solution is 10-15 vt%, and it is free of impurities.
[0028] Furthermore, the concentration of the ethylene glycol solution is 10-15 vt.
[0029] Furthermore, the activated clay is of industrial grade, with an adsorption capacity of ≥15 mL / 100 g and a particle size of 100-200 mesh.
[0030] Furthermore, when used in mild regions, the crude glycerin component is 190-210 parts by weight, and the agricultural waste fiber component is 59-61 parts by weight.
[0031] Furthermore, when used in mild regions, the crude glycerin component comprises 200 parts by weight and the agricultural waste fiber component comprises 60 parts by weight.
[0032] Furthermore, temperate regions are those where the lowest winter temperatures range from -5°C to -18°C.
[0033] Furthermore, when used in frigid regions, the crude glycerin component is 210-230 parts by weight, and the agricultural waste fiber component is 64-66 parts by weight.
[0034] Furthermore, when used in frigid regions, the crude glycerin component comprises 220 parts by weight, and the agricultural waste fiber component comprises 65 parts by weight.
[0035] Furthermore, frigid regions are those where the lowest winter temperature is below -18°C.
[0036] The above-mentioned method for preparing environmentally friendly de-icing agents based on agricultural and forestry waste includes the following steps: S1. Dry the ash from agricultural and forestry waste combustion by sieving, and add it to the organic waste liquid from food processing while stirring. After stirring, let it stand to obtain a suspension. S2. Stir, filter and concentrate the suspension obtained in step S1 to obtain potassium acetate solution. Mix the potassium acetate solution with polyol and heat to obtain solid block. S3. Crush the solid block obtained in step S2, add filler, mix to obtain a mixture, then soak agricultural waste fiber and disperse it into fiber pulp and add it to the mixture. After sieving, add synthetic pulp, polyacrylate water absorbent, activated clay and binder and stir. Sieving again, drying and crushing to obtain an environmentally friendly snow melting agent based on agricultural and forestry waste.
[0037] Furthermore, in step S1, the stirring rate is 250-350 r / min.
[0038] Furthermore, in step S1, the stirring rate is 300 r / min.
[0039] Furthermore, in step S1, after adding the ingredients, continue stirring for 5-15 minutes.
[0040] Furthermore, in step S1, after the addition is complete, continue stirring for 10 minutes.
[0041] The beneficial effect of taking the above-mentioned further measures is to ensure that the wood ash and the lees are in full contact.
[0042] Furthermore, in step S1, the sample is placed in a constant temperature settling tank.
[0043] Furthermore, in step S1, the temperature during the settling period is 20-25 ℃.
[0044] Furthermore, in step S1, the settling time is 1-2 hours.
[0045] Furthermore, in step S1, the settling time is 1.5 h.
[0046] The beneficial effect of taking the above-mentioned further measures is that it allows the potassium carbonate in the wood ash to fully dissolve in the lees.
[0047] Further, in step S2, the mixture is stirred in the reactor.
[0048] Furthermore, in step S2, the stirring temperature is 50-60 ℃, the stirring speed is 150-250 r / min, and the stirring time is 30-50 min.
[0049] Furthermore, in step S2, the stirring temperature is 55 ℃, the stirring speed is 200 r / min, and the stirring time is 40 min.
[0050] The beneficial effect of taking the above-mentioned further measures is that potassium carbonate and acetic acid undergo a neutralization reaction: K2CO3 + 2CH3COOH = 2CH3COOK + CO2↑ + H2O, producing potassium acetate.
[0051] Furthermore, in step S2, the carbon dioxide generated during the stirring process is collected by the exhaust gas collection device.
[0052] Furthermore, in step S2, the reaction vessel is filtered when the temperature drops to 25-30℃.
[0053] Furthermore, in step S2, the filter is passed through a plate and frame filter press.
[0054] Furthermore, in step S2, the filtration pressure of the plate and frame filter press is 0.2-0.4 MPa, and the filtration speed is 40-60 L / h.
[0055] Furthermore, in step S2, the filtration pressure of the plate and frame filter press is 0.3 MPa, and the filtration speed is 50 L / h.
[0056] The beneficial effects of taking the above-mentioned further measures are: removing solid residues (mainly unreacted impurities) and obtaining a clear solution containing potassium acetate.
[0057] Furthermore, in step S2, the residue generated from filtration can be dried and recycled as raw material for organic fertilizer, achieving zero discharge of solid waste.
[0058] Furthermore, in step S2, when the potassium acetate concentration in the clarified liquid is <30 wt%, vacuum evaporation concentration is performed.
[0059] Furthermore, in step S2, vacuum evaporation concentration is carried out in a vacuum evaporator.
[0060] Furthermore, in step S2, the temperature during vacuum evaporation and concentration is 55-65 ℃, and the vacuum degree is 0.07-0.09 MPa.
[0061] Furthermore, in step S2, the temperature during vacuum evaporation concentration is 60 ℃ and the vacuum degree is 0.08 MPa.
[0062] Furthermore, in step S2, the evaporation rate is 90-110 L / h.
[0063] Furthermore, in step S2, the evaporation rate is 100 L / h.
[0064] Furthermore, in step S2, evaporation is stopped when the concentration of potassium acetate solution is ≥30 wt%.
[0065] Furthermore, in step S2, the potassium acetate solution is transferred to an insulated storage tank for later use.
[0066] Furthermore, in step S2, the temperature in the insulated storage tank is 35-45 ℃.
[0067] Furthermore, in step S2, the temperature in the insulated storage tank is 40 ℃.
[0068] The beneficial effect of taking the above-mentioned further measures is to prevent solidification.
[0069] Further, in step S2, the mixture is mixed in a twin-helix mixer.
[0070] Furthermore, in step S2, the mixing temperature is 62-68℃, the rotation speed is 140-160 r / min, and the time is 14-16 min.
[0071] Furthermore, in step S2, the mixing temperature is 65℃, the rotation speed is 150 r / min, and the time is 15 min.
[0072] Furthermore, in step S2, the temperature of the mixing system is raised by jacket heating.
[0073] Further, in step S2, the mixture is cooled to 20-25 °C to obtain a solid block.
[0074] Furthermore, in step S3, the material is pulverized in a universal pulverizer.
[0075] Furthermore, in step S3, the particles are crushed to a particle size ≤ 1 mm.
[0076] Furthermore, in step S3, the mixture is mixed in a three-dimensional mixer.
[0077] Furthermore, in step S3, the mixing speed is 190-210 r / min, the temperature is 20-25 ℃, and the time is 15-25 min.
[0078] Furthermore, in step S3, the mixing speed is 200 r / min, the temperature is 23 ℃, and the time is 20 min.
[0079] The beneficial effects of adopting the above-mentioned further solutions are: diatomaceous earth or bentonite is uniformly coated on the surface of the particles, resulting in a uniform mixed powder after discharge; diatomaceous earth can not only prevent powder from clumping, but its porous structure can also adsorb some snow-melting components, enhancing the adhesion and slow-release effect of subsequent products.
[0080] Furthermore, in step S3, more than 90% of the mixed powder has a particle size of 100-200 mesh.
[0081] Furthermore, in step S3, agricultural waste fibers are soaked in clean water.
[0082] Furthermore, in step S3, the mass-to-volume ratio of agricultural waste fiber to clean water is 1 kg: 7-9 L.
[0083] Furthermore, in step S3, the mass-to-volume ratio of agricultural waste fiber to clean water is 1 kg: 8 L.
[0084] Furthermore, in step S3, the soaking time is 1.5-2.5 h, during which the mixture is stirred for 4-6 min every 25-35 min, and the stirring rate is 150-250 r / min.
[0085] Furthermore, in step S3, the soaking time is 2 hours, during which the mixture is stirred for 5 minutes every 30 minutes at a stirring rate of 200 r / min.
[0086] The beneficial effect of taking the above-mentioned further measures is to ensure that the fibers fully absorb water and swell.
[0087] Furthermore, in step S3, after soaking, the fibers are dispersed into a uniform fiber slurry using a high-speed disperser.
[0088] Furthermore, in step S3, the speed of the high-speed disperser is 1400-1600 r / min, and the stirring time is 5-15 min.
[0089] Furthermore, in step S3, the high-speed disperser rotates at 1500 r / min and the stirring time is 10 min.
[0090] Furthermore, in step S3, the fiber pulp is passed through an 80-mesh sieve.
[0091] Furthermore, in step S3, the stirring speed is 250-350 r / min, and the stirring time is 10-20 min.
[0092] Furthermore, in step S3, the stirring speed is 300 r / min and the stirring time is 15 min.
[0093] Furthermore, in step S3, the sample is passed through an 80-mesh sieve again.
[0094] The beneficial effects of adopting the above-mentioned further measures are: secondary screening to further remove impurities and large particles.
[0095] Further, in step S3, the product is placed in a hot air oven for drying.
[0096] Furthermore, in step S3, the drying temperature is 150-170 ℃, the time is 0.5-1.5 h, and the product is turned over once every 10-20 minutes during the process.
[0097] Furthermore, in step S3, the drying temperature is 160 ℃ and the time is 1 h, during which the product is turned over once every 15 min.
[0098] Furthermore, in step S3, after cooling to room temperature, the material is pulverized to a particle size ≤ 0.5 mm using a universal pulverizer.
[0099] In summary, the present invention has the following beneficial effects: 1. The present invention has significant cost advantages. It efficiently converts agricultural and forestry waste combustion ash and alcohol residue into potassium acetate, replacing high-cost potassium acetate crystals. Combined with the recycling of agricultural waste such as corn stalk fiber, the total cost of 1 ton of finished snow melting agent is controlled at 3423 yuan, which is 25-30% lower than the existing technology. The reaction residue and screening fine powder can be recycled, realizing resource recycling.
[0100] 2. The porous structure of straw fiber and rice husk fiber coagulant works synergistically with the adsorption properties of diatomaceous earth to adsorb snow-melting components, preventing rapid loss and extending the snow-melting time to 8-12 hours, an improvement of over 50% compared to existing technologies, reducing the number of re-spreading operations. The porous structure of fillers such as diatomaceous earth, bentonite, and zeolite powder, combined with the entanglement properties of straw fiber, increases the adhesion rate of snow-melting agent particles to the road surface to over 90%. Enhanced adhesion reduces waste, and the loss rate due to vehicle runoff is reduced to below 5%, significantly improving material utilization. The porous structure of polyacrylate water-absorbing agent and straw fiber locks in some of the snow-melting moisture, delaying moisture evaporation and loss. The probability of secondary icing on the road surface after snow melting is reduced by over 80%, providing excellent anti-icing effects and improving traffic safety.
[0101] 3. The methyl glucoside used in this invention is non-toxic and has a biodegradability rate of ≥95%. The ash from the combustion of agricultural and forestry waste and the fiber from agricultural waste are agricultural wastes, and there is no emission of toxic or harmful substances during the production process. The product does not contain chloride salts, and its corrosion rate to road concrete is ≤0.02 mm / a, and its corrosion rate to metal is ≤0.005 mm / a, which is far below the industry standard.
[0102] 4. The snow-melting efficiency of this invention is stable. The synergistic effect of potassium acetate, methyl glucoside, and crude glycerol, among other polyols, can lower the freezing point to below -20°C. In low-temperature environments of -10°C to -20°C, the snow-melting rate remains at 0.8-1.2 kg / (m²·h), meeting the needs of extremely cold regions. The composite particles have a compressive strength ≥1.5 MPa, are not prone to clumping or breakage, and are easy to use. Crude glycerol, as a polyol, contains three -OH groups, which disrupt the ice and snow lattice through hydrogen bonding, allowing its snow-melting performance to be precisely adapted to the needs of temperate / subtropical and extremely cold regions. Furthermore, crude glycerol is derived from biodiesel byproducts, is inexpensive, essentially non-toxic, and has a biodegradability rate ≥90%. After purification with activated clay, it has low impurity content, does not pollute soil or groundwater, and will not cause infrastructure corrosion, demonstrating good environmental performance and conforming to the concept of resource recycling. In addition, by adjusting the amount of crude glycerol and the ratio of solidifying materials, it can be adapted to different temperature ranges from -10°C to -18°C, and the raw material supply is sufficient, enabling large-scale industrial production. Detailed Implementation
[0103] The principles and features of this invention are described below. The examples given are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer should be followed. Reagents or instruments whose manufacturers are not specified are all commercially available products.
[0104] Example 1 An environmentally friendly de-icing agent based on agricultural and forestry waste comprises the following components by weight: 200 parts wood ash, 800 parts alcohol residue, 180 parts liquid methyl glucoside, 150 parts diatomaceous earth, 60 parts corn stalk fiber, 7.5 parts synthetic pulp, 7.5 parts polyacrylate absorbent, and 100 parts alcohol solution.
[0105] The above-mentioned method for preparing environmentally friendly de-icing agents based on agricultural and forestry waste includes the following steps: S1. Pass the wood ash through an 80-mesh sieve. The potassium content is 10 wt%. Place it in a hot air drying oven and dry it at 60 ℃ for 1 h to make the moisture content 5 wt%. Add the wood ash to the alcohol residue. The alcohol residue has an ethanol concentration of 35 vt and an acetic acid content of 20000 mg / L. Add the wood ash while stirring at a stirring rate of 300 r / min. After the addition is complete, continue stirring for 10 min to ensure that the wood ash and alcohol residue are in full contact. After stirring, let it stand in a constant temperature settling tank at 23 ℃ for 1.5 h to obtain a suspension. S2. The suspension obtained in step S1 is pumped into a reactor using a centrifugal pump. The reactor inlet is closed, and the stirring device is started. The stirring temperature is 55 ℃, the stirring rate is 200 r / min, and the stirring time is 40 min. During the stirring process, carbon dioxide generated is collected by a tail gas collection device. When the reactor temperature drops to 28 ℃, the solution is filtered through a plate and frame filter press to obtain a potassium acetate solution. The filtration pressure of the plate and frame filter press is 0.3 MPa, and the filtration speed is 50 L / h. The residue produced by filtration can be dried and recycled as an organic fertilizer raw material. The concentration of the potassium acetate solution is 20 wt%. Vacuum evaporation concentration is carried out in a vacuum evaporator. The vacuum evaporation concentration temperature is 60 ℃, the vacuum degree is 0.08 MPa, and the evaporation rate is 100 L / h. When the potassium acetate concentration reaches 30 wt%, evaporation is stopped, and the potassium acetate solution is transferred to an insulated storage tank for later use. The temperature in the insulated storage tank is 40 ℃. Potassium acetate and liquid methyl glucoside were mixed in a double helix mixer at ℃. The mixture was heated by jacket heating. The mixing temperature was 65℃, the rotation speed was 150 r / min, and the time was 15 min. After cooling to room temperature, a solid block was obtained. S3. The solid lumps obtained in step S2 are pulverized into particles with a diameter ≤1mm in a universal pulverizer. Diatomaceous earth is added and mixed in a three-dimensional mixer at a speed of 200 r / min, a temperature of 23 ℃, and a time of 20 min to obtain a mixture. Then, corn stalk fibers are soaked in water for 2 h, stirring for 5 min every 30 min at a stirring speed of 200 r / min. The mass-to-volume ratio of corn stalk fibers to water is 1 kg:8 L. Then, a high-speed disperser is started at a speed of 1500 r / min and stirred for 10 min to disperse the corn stalk fibers into a fiber slurry. This slurry is added to the mixture and passed through an 80-mesh sieve. Then, synthetic pulp, polyacrylate water absorbent, and 12 vt% alcohol solution are added and stirred at a speed of 300 r / min for 15 min. The mixture is then passed through an 80-mesh sieve again and placed in a hot air oven for drying at a temperature of 160 ℃ for 1 h, turning it over every 15 min. After cooling to room temperature, the mixture is pulverized into particles with a diameter ≤0.5 mm using a universal pulverizer. mm, an environmentally friendly de-icing agent based on agricultural and forestry waste.
[0106] Example 2 An environmentally friendly de-icing agent based on agricultural and forestry waste comprises the following components by weight: 150 parts straw ash, 750 parts vinegar residue, 200 parts crude glycerin, 150 parts bentonite, 60 parts wheat straw fiber, 7 parts synthetic pulp, 7 parts polyacrylate water absorbent, 90 parts ethylene glycol solution, and 5 parts activated clay.
[0107] The above-mentioned method for preparing environmentally friendly de-icing agents based on agricultural and forestry waste includes the following steps: S1. Pass the straw ash through an 80-mesh sieve. The potassium content is 10 wt%. Place it in a hot air drying oven and dry it at 60 ℃ for 1 h to make the moisture content 5 wt%. Add the straw ash to the vinegar residue. The vinegar residue has an ethanol concentration of 35 vt and an acetic acid content of 20000 mg / L. Add the straw ash while stirring at a stirring rate of 250 r / min. After the addition is complete, continue stirring for 5 min to ensure that the straw ash and vinegar residue are in full contact. After stirring, let it stand in a constant temperature settling tank at 20 ℃ for 1 h to obtain a suspension. S2. The suspension obtained in step S1 is pumped into a reactor using a centrifugal pump. The reactor inlet is closed, and the stirring device is started. The stirring temperature is 50 ℃, the stirring rate is 150 r / min, and the stirring time is 30 min. During the stirring process, the carbon dioxide generated is collected by the exhaust gas collection device. When the reactor temperature drops to 25 ℃, the solution is filtered through a plate and frame filter press to obtain a potassium acetate solution. The filtration pressure of the plate and frame filter press is 0.2 MPa, and the filtration speed is 40 L / h. The residue produced by filtration can be dried and recycled as an organic fertilizer raw material. The concentration of the potassium acetate solution is measured to be 25 wt%. Vacuum evaporation and concentration are carried out in a vacuum evaporator. The vacuum evaporation and concentration temperature is 55 ℃, the vacuum degree is 0.07 MPa, and the evaporation rate is 90 L / h. When the potassium acetate concentration reaches 30 wt%, evaporation is stopped, and the potassium acetate solution is transferred to an insulated storage tank for later use. The temperature in the insulated storage tank is 35 ℃. Potassium acetate and crude glycerol were mixed in a double-screw mixer at 62 °C. The mixture was heated by jacket heating. The mixing temperature was 62 °C, the speed was 140 r / min, and the time was 14 min. After cooling to room temperature, a solid block was obtained. S3. The solid lumps obtained in step S2 are pulverized into particles with a particle size ≤1mm in a universal pulverizer. Bentonite is added and mixed in a three-dimensional mixer at a speed of 190 r / min, a temperature of 20 ℃, and a time of 15 min to obtain a mixture. Then, wheat straw fiber is soaked in water for 1.5 h, stirring for 4 min every 25 min at a stirring speed of 150 r / min. The mass-to-volume ratio of wheat straw fiber to water is 1 kg:7 L. Then, a high-speed disperser is started at a speed of 1400 r / min and stirred for 5 min to disperse the wheat straw fiber into a fiber slurry. This slurry is added to the mixture and passed through an 80-mesh sieve. Then, synthetic pulp, polyacrylate absorbent, activated clay, and 10 wt% ethylene glycol solution are added and stirred at a speed of 250 r / min for 10 min. The mixture is then passed through an 80-mesh sieve again and placed in a hot air oven for drying at a temperature of 150 ℃ for 0.5 hours. The mixture is turned over every 10 minutes during the process. After cooling to room temperature, it is pulverized with a universal pulverizer to a particle size ≤0.5 mm to obtain an environmentally friendly de-icing agent based on agricultural and forestry waste.
[0108] Example 3 An environmentally friendly de-icing agent based on agricultural and forestry waste comprises the following components in parts by weight: 250 parts dead branch ash, 850 parts alcohol residue, 220 parts liquid methyl glucoside, 200 parts zeolite powder, 65 parts rice husk fiber, 8 parts synthetic pulp, 8 parts polyacrylate water absorbent, and 110 parts alcohol solution.
[0109] The above-mentioned method for preparing environmentally friendly de-icing agents based on agricultural and forestry waste includes the following steps: S1. Pass the dead branch ash through an 80-mesh sieve. The potassium content is 10 wt%. Place it in a hot air drying oven and dry it at 60 ℃ for 1 h to make the moisture content 5 wt%. Add the dead branch ash to the alcohol residue. The alcohol residue has an ethanol concentration of 35 vt and an acetic acid content of 20000 mg / L. Add it while stirring at a stirring rate of 350 r / min. After the addition is complete, continue stirring for 15 min to ensure that the dead branch ash and alcohol residue are in full contact. After stirring, let it stand in a constant temperature settling tank at 25 ℃ for 2 h to obtain a suspension. S2. The suspension obtained in step S1 is pumped into a reactor using a centrifugal pump. The reactor inlet is closed, and the stirring device is started. The stirring temperature is 60 ℃, the stirring rate is 250 r / min, and the stirring time is 50 min. During the stirring process, carbon dioxide generated is collected by a tail gas collection device. When the reactor temperature drops to 30 ℃, the solution is filtered through a plate and frame filter press to obtain a potassium acetate solution. The filtration pressure of the plate and frame filter press is 0.4 MPa, and the filtration speed is 60 L / h. The residue produced by filtration can be dried and recycled as an organic fertilizer raw material. The concentration of the potassium acetate solution is measured to be 22 wt%. Vacuum evaporation concentration is carried out in a vacuum evaporator. The vacuum evaporation concentration temperature is 65 ℃, the vacuum degree is 0.09 MPa, and the evaporation rate is 110 L / h. When the potassium acetate concentration reaches 30 wt%, evaporation is stopped, and the potassium acetate solution is transferred to an insulated storage tank for later use. The temperature in the insulated storage tank is 45 ℃. Potassium acetate and liquid methyl glucoside were mixed in a double helix mixer at ℃. The mixture was heated by jacket heating to a temperature of 68℃, a speed of 160 r / min, and a time of 16 min. After cooling to room temperature, a solid block was obtained. S3. The solid block obtained in step S2 is pulverized into particles with a particle size ≤1mm in a universal pulverizer. Zeolite powder is added and mixed in a three-dimensional mixer at a speed of 210 r / min, a temperature of 25 ℃, and a time of 25 min to obtain a mixture. Then, rice husk fiber is soaked in water for 2.5 h, with stirring for 6 min every 35 min at a stirring speed of 250 r / min. The mass-to-volume ratio of rice husk fiber to water is 1 kg:9 L. Then, a high-speed disperser is started at a speed of 1600 r / min and stirred for 15 min to disperse the rice husk fiber into a fiber pulp. This pulp is added to the mixture and passed through an 80-mesh sieve. Then, synthetic pulp, polyacrylate water absorbent, and 15 vt% alcohol solution are added and stirred at a speed of 350 r / min for 20 min. The pulp is passed through an 80-mesh sieve again and placed in a hot air oven for drying at a temperature of 170 ℃ for 1.5 h, with stirring every 20 min. After turning the mixture once a minute and cooling it to room temperature, crush it with a universal pulverizer to a particle size ≤0.5 mm to obtain an environmentally friendly de-icing agent based on agricultural and forestry waste.
[0110] Comparative Example 1 A solid environmentally friendly de-icing agent is prepared by the following steps: First, 50g of liquid methyl glycoside and 50g of alcohol residue are mixed and heated to 70°C. After cooling, 50g of silica powder is added and stirred thoroughly. Then, 50g of calcium carbonate powder and 10g of methyl glycoside or hydrogel-filled paper pulp coagulant are thoroughly mixed in a mixer. The two are then mixed to obtain the de-icing agent.
[0111] Comparative Example 2 An environmentally friendly low-chlorine de-icing agent comprises the following components by weight: 18 parts concentrated acetic acid solution, 100 parts wood ash, 0.5 parts urea, 9 parts glycerin, 2 parts calcium formate, and 2 parts sodium benzoate.
[0112] The preparation method of the above-mentioned environmentally friendly low-chlorine de-icing agent includes the following steps: (1) Take the waste liquid from the bread and pastry factory, and add α under the conditions of pH 6.0 and temperature 60℃. Amylase, β-amylase, and saccharifying amylase were hydrolyzed for 45 minutes to obtain a glucose solution.
[0113] (2) Mix glucose solution with yeast strain JZ and let it ferment for 6 days at pH 4.0 and temperature 38℃ to obtain ethanol solution.
[0114] (3) Add acetic acid bacteria strain A3 to the ethanol solution and ferment for 8 days at pH 5.5 and temperature 35℃ to obtain acetic acid solution, which is then concentrated to 50% acetic acid mass concentration.
[0115] (4) Add sufficient wood ash to the concentrated acetic acid solution, stir and soak, then heat in a water bath at 85°C for 75 minutes to obtain a potassium acetate mixed solution.
[0116] (5) Add urea, glycerin, calcium formate and sodium benzoate according to the formula, and stir evenly at a constant stirring speed to obtain the snow melting agent.
[0117] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, the components are directly mixed in a dry state.
[0118] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 does not contain wood ash.
[0119] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that Comparative Example 5 does not contain liquid methyl glucoside.
[0120] Experimental Example 1 To compare the snow melting rate of the snow melting agents prepared in Examples 1-3 and Comparative Examples 1-5, the ice tray method was used. 50g of distilled water was frozen into ice trays of uniform thickness in a freezer at -15℃. Six ice trays were prepared, and 1g of the snow melting agents prepared in Examples 1-3 and Comparative Examples 1-5 was placed in the center of the surface of each ice tray. The time when the ice tray completely melted was recorded. The results are shown in Table 1.
[0121] Table 1. Comparison of snow melting time at -15℃
[0122] As shown in Table 1, compared with Comparative Example 1, the snow melting rate of the present invention is increased by approximately 37%; compared with Comparative Example 2, the snow melting rate of the present invention is increased by approximately 18%. Furthermore, the snow melting rate of the present invention is much higher than that of Comparative Examples 3-5, indicating that wood ash and liquid methyl glucoside have a synergistic effect, thereby increasing the snow melting rate.
[0123] Experimental Example 2 To test the metal corrosivity of the de-icing agent, the de-icing agents prepared in Examples 1-3 and Comparative Examples 1-5 were prepared into solutions with a concentration of 5 wt%. Carbon steel sheets were ground, cleaned, dried, and weighed (W1). They were then completely immersed in the solution and left at room temperature for 72 h. The steel sheets were then removed, and the corrosion products were removed with pickling solution. After cleaning, drying, and weighing, the steel sheets were removed (W2).
[0124] Corrosion rate calculation formula: Metal corrosion rate = (W1 - W2) / (Surface area × Time) The metal corrosion rates of the de-icing agents prepared in Example 1 and Comparative Examples 1-2 are shown in Table 2.
[0125] Table 2 Comparison of Metal Corrosion Rates
[0126] As shown in Table 2, the metal corrosion rate of the present invention is significantly reduced compared with that of comparative examples 1-5.
[0127] Experimental Example 3 By simulating the actual scenario of snow-melting agent seeping into the soil with snow-melting water, and through "simulated snow-melting water irrigation + survival rate quantification" under unified conditions, the impact of the snow-melting agent of this invention on vegetation growth is compared with that of existing technologies and traditional products, thus verifying the environmentally friendly characteristics of this invention.
[0128] I. Experimental Materials and Equipment (a) Experimental Samples 1. Samples of the present invention: the de-icing agent prepared in Example 1 (T1), the de-icing agent prepared in Example 2 (T2), and the de-icing agent prepared in Example 3 (T3); 2. Control sample: Blank control (CK): Distilled water without de-icing agent; Comparison with existing technologies: snow melting agent prepared in Comparative Example 1 (CK1) and snow melting agent prepared in Comparative Example 2 (CK2). Traditional product comparison (CK3): Commercially available sodium chloride-based de-icing agent (chlorine content ≥95%).
[0129] (II) Vegetation and Substrate 1. Vegetation selection: Select ryegrass (seed germination rate ≥95%), which is commonly found around roads and is sensitive to soil conditions, and purchase it uniformly and in consistent batches; 2. Soil substrate: Collect surface soil (0-20cm) from urban road green belts, remove impurities and pass through a 2 mm sieve, adjust the initial moisture content to 60% of field capacity, and test the initial pH value (6.2-6.8) and EC value (≤0.5 mS / cm) to ensure that the substrate conditions of each group are uniform.
[0130] II. Experimental Design 1. Group setup: Each group has 3 parallel replicates, for a total of 5 groups × 3 replicates = 15 pots; 2. Sample solution preparation: Referring to the unified standard of "5 wt% concentration" in metal corrosion experiments and combined with actual snow melting scenarios, each snow melting agent sample was prepared into a 5 wt% simulated snow melting water (core concentration) using distilled water. The blank control group used distilled water. 3. Planting conditions: Fill each pot with 1.5 kg of soil substrate, sow 50 ryegrass seeds evenly, cover with 0.5 cm of soil, and pre-cultivate for 7 days (to ensure seed germination and adaptation to the environment) before watering.
[0131] III. Experimental Procedure 1. Irrigation treatment: After the pre-cultivation period, the corresponding group was irrigated with simulated snow melt water once a week, with an amount of 150mL / pot each time (to ensure full infiltration into the soil and no runoff). The blank control group was irrigated with an equal amount of distilled water. The treatment was continued for 4 weeks (from the simulated snow melt period to the vegetation recovery stage). 2. Environmental control: The temperature in the artificial climate chamber is maintained at 25℃ during the day and 18℃ at night, with a relative humidity of 60-70%. If the soil moisture content is lower than 50% of field capacity, distilled water is added to the set value to avoid drought interference. 3. Data Detection: Referring to the quantitative logic of the "72 h immersion test" in the metal corrosion experiment, the number of surviving plants in each group was recorded 14 days and 28 days after the irrigation treatment (plants with a height ≥2 cm and no wilting leaves were considered to be surviving). After the experiment (28 days), soil samples were collected from each group to test pH and EC values and compare the changes with the initial values. 4. Survival rate calculation: Survival rate = (number of surviving plants / total number of seeds) × 100%, take the average value of parallel groups.
[0132] Precautions: All operations should follow the "single variable principle," with only the type of de-icing agent as the variable, while keeping other conditions consistent; the irrigation rate should be uniform to avoid solution overflow and concentration deviation; parallel groups should operate synchronously, data records should be accurate and true, and original records should be retained for future reference.
[0133] IV. Recording and Analysis of Experimental Results The experimental results are shown in Table 3.
[0134] Table 3 Comparison of Vegetation Survival Rate and Soil Indicators
[0135] As shown in Table 3, (1) the 28-day survival rate of the snow melting agent provided by the present invention is ≥82%, which is significantly higher than that of the existing technology control group (CK1-CK2) and the traditional chloride salt control group (CK3), and there is no significant difference from the blank control group (CK); (2) the changes in soil pH and EC values in the present invention group are much smaller than those in the existing technology control group, indicating that it has less impact on the soil environment and thus ensures the survival of vegetation.
[0136] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An environmentally friendly de-icing agent based on agricultural and forestry waste, characterized in that, It includes the following components by weight: 150-250 parts of agricultural and forestry waste combustion ash, 750-850 parts of food processing organic waste liquid, 180-220 parts of polyol, 100-200 parts of filler, 60-65 parts of agricultural waste fiber, 7-8 parts of synthetic pulp, 7-8 parts of polyacrylate water absorbent, 90-110 parts of binder, and 0-5 parts of activated clay.
2. The environmentally friendly snow-melting agent based on agricultural and forestry waste as described in claim 1, characterized in that, It includes the following components by weight: 200 parts of agricultural and forestry waste combustion ash, 800 parts of food processing organic waste liquid, 180 parts of polyol, 150 parts of filler, 60 parts of agricultural waste fiber, 7.5 parts of synthetic pulp, 7.5 parts of polyacrylate water absorbent, 100 parts of binder, and 5 parts of activated clay.
3. The environmentally friendly snow-melting agent based on agricultural and forestry waste as described in claim 1 or 2, characterized in that, The ash from the combustion of agricultural and forestry waste is one of the following: wood ash, straw ash, and dead branch ash.
4. The environmentally friendly snow-melting agent based on agricultural and forestry waste as described in claim 1 or 2, characterized in that, The organic waste liquid from food processing is alcohol residue or vinegar residue.
5. The environmentally friendly snow-melting agent based on agricultural and forestry waste as described in claim 1 or 2, characterized in that, The polyol is a liquid methyl glucoside or crude glycerol.
6. The environmentally friendly snow-melting agent based on agricultural and forestry waste as described in claim 1 or 2, characterized in that, The filler is one of diatomaceous earth, bentonite, and zeolite powder.
7. The environmentally friendly snow-melting agent based on agricultural and forestry waste as described in claim 1, characterized in that, The agricultural waste fiber is one of corn stalk fiber, wheat stalk fiber, and rice husk fiber.
8. The environmentally friendly snow-melting agent based on agricultural and forestry waste as described in claim 7, characterized in that, The adhesive is an alcohol solution or an ethylene glycol solution.
9. The method for preparing the environmentally friendly de-icing agent based on agricultural and forestry waste according to claims 1-8, characterized in that, Includes the following steps: S1. Dry the ash from agricultural and forestry waste combustion by sieving, and add it to the organic waste liquid from food processing while stirring. After stirring, let it stand to obtain a suspension. S2. Stir, filter and concentrate the suspension obtained in step S1 to obtain potassium acetate solution. Mix the potassium acetate solution with polyol and heat to obtain solid block. S3. Crush the solid block obtained in step S2, add filler, mix to obtain a mixture, then soak agricultural waste fiber and disperse it into fiber pulp and add it to the mixture. After sieving, add synthetic pulp, polyacrylate water absorbent, activated clay and binder and stir. Sieving again, drying and crushing to obtain an environmentally friendly snow melting agent based on agricultural and forestry waste.
10. The method for preparing the environmentally friendly de-icing agent based on agricultural and forestry waste as described in claim 9, characterized in that, In step S2, the stirring temperature is 50-60 ℃, the stirring speed is 150-250 r / min, and the stirring time is 30-50 min.